Efficacy of selective laser trabeculoplasty in primary angle closure disease. (November 2018) - Raj, Srishti; Tigari, Basavraj; Faisal, T.; Gautam, Natasha; Kaushik, Sushmita; Ichhpujani, Parul; Pandav, Surinder S.; Ram, Jagat
Abstract Background To study the role of selective laser trabeculoplasty (SLT) in intraocular pressure (IOP) reduction in post-laser iridotomy primary angle-closure disease patients with inadequately controlled IOP. Methods In this prospective cross-sectional study, 34 patients with primary angle-closure disease with post-laser iridotomy open angles up to at least 180° were recruited. Following SLT, patients were examined at 1 day, 1 week, 1 and 3 months, 6 months and 1 year post SLT. Results Data of 34 patients (34 eyes; 8 males and 26 females), with a mean age of 57.80 ± 6.44 years, were analysed. The reduction in IOP at each follow-up visit was significant (p  < 0.001). The maximum reduction in IOP was noticed on post-laser day 1 and the least reduction was noticed 1 week post laser. Post-SLT range of IOP reduction varied from 9 to 46% at 1 year, which indicates the variability of a response to SLT. Mean IOP in both primary angle closure (PAC) and primary angle closure glaucoma (PACG) groups was comparable at all visits except at post-SLT week 1 when IOP in the PACG group was significantly higher than that in the PAC group (p  = 0.035). None of the patients complained of pain and/or discomfort or had any clinically significant anterior segment inflammation on any of the follow-up visits. None of the patients underwent repeat SLT or surgery. The mean pre-SLT and post-SLT visual field index at 1-year follow-up was 95.47 ± 3.58 and 95.90 ± 4.13, respectively, which was not significant (p  = 0.84). Conclusions High baseline IOP significantly correlated with reduction in IOP. Our results suggest that SLT is a safe, cost-effective modality for reducing IOP in primary angle-closure disease with patent laser iridotomy with a visible trabecular meshwork.